Levantamento das características dos pacientes atendidos no serviço de oxigenoterapia da Faculdade de Medicina de Botucatu-UNESP - Alves, Maria Virgínia Martins Faria Faddul [UNESP]; Godoy, Irma de [UNESP]; Luppi, Cláudia Helena Bronzato [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
This work was held from January 1997 to January 1999 with 66 patients registered in the Oxygen Therapy Service at the Medical School in Botucatu (FMB) – UNESP. The aim of this study was to evaluate the patients’ health and overall characteristics as well as the oxygen delivery and use conditions. The average age was 61.2 ± 10.1 years, 61% men, with poor education level, low income and social conditions. Chronic obstructive pulmonary disease (COPD) was the major pathology found, corresponding to 78.2% diagnoses. According to the arterial blood gasometry results (PaO2 = 46.14 ± 9.07 mmHg, PaCO2 = 45.80 ± 7.99 mmHg and SaO2 = 79.25 ± 11.44%), all patients have met the indication and utilization criteria for long-term oxygen therapy (LTOT) in agreement with the national and international consensus committee. Patients were delivered oxygen by means of a gas cylinder and by nasal cannula . The municipal public services were in charge of the oxygen delivery for 80.5% patients. The oxygen flow was used following recommendations, although the number of hours was less than the prescribed one; only 8.4% patients used LTOT more than 12 hours a day. Based on this study some arrangements regarding these patients’ care have been carried out, such as the replacement of the gas cylinder by the oxygen concentrator, leading to an improved care quality. The oxygen therapy service from the Medical School became a reference symbol for the Health Secretary in Botucatu as well as for LTOT prescription and patients’ follow-up. CONCLUSION : The majority of the patients who have undertaken long term oxygen therapy are of the male sex, COPD carriers and have not followed the treatment as they have been prescribed.

O presente trabalho foi realizado no período de janeiro de 1997 a janeiro de 1999 com 66 pacientes cadastrados no Serviço de Oxigenoterapia da Faculdade de Medicina de Botucatu (FMB) - UNESP. O objetivo foi conhecer os pacientes, suas características gerais e de saúde, bem como as condições de fornecimento e uso do oxigênio. A média de idade foi de 61,2 ± 10,1 anos, 61% eram do sexo masculino, apresentavam grau de escolaridade baixo e condição sócio-econômica desfavorável. A doença pulmonar obstrutiva crônica (DPOC) foi a principal patologia encontrada, correspondendo a 78,2% dos diagnósticos. De acordo com os resultados da gasometria arterial (PaO2 = 46,14 ± 9,07 mmHg, PaCO2 = 45,80 ± 7,99 mmHg e SaO2 = 79,25 ± 11,44%), todos os pacientes preenchiam os critérios de indicação e uso de oxigenoterapia domiciliar prolongada (ODP) de acordo com os consensos nacional e internacional. Os pacientes recebiam oxigênio por meio de cilindro de gás e utilizavam cateter nasal tipo óculos. As prefeituras eram responsáveis pelo fornecimento de oxigênio para 80,5% dos pacientes. O fluxo de oxigênio era utilizado de acordo com o prescrito, porém o tempo de uso, em horas, era menor que o recomendado; somente 8,4% dos pacientes utilizavam ODP mais que 12 horas por dia. Foram realizadas algumas modificações no atendimento destes pacientes, pois o Serviço de Oxigenoterapia da FMB tornou-se referência para a Secretaria de Saúde do Município de Botucatu, bem como para indicação da ODP e acompanhamento dos pacientes; o cilindro de gás foi substituído pelo concentrador de oxigênio, melhorando a qualidade de atendimento. Conclusão – a maioria dos pacientes que fazem uso de ODP são do sexo masculino, portadores de DPOC e não fazem o tratamento da maneira prescrita.
Profile of patients attending the oxygen therapy service at the medical school in Botucatu-UNESP
Keywords: Long-term oxygen therapy; Chronic obstructive pulmonary disease; Oxygen flow; Biológicas; Saúde; Oxigenoterapia domiciliar prolongada; Doença pulmonar obstrutiva crônica; Fluxo de oxigênio